2018
DOI: 10.1002/app.46835
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PMA–TPAI and PVAc–TPAI solid polymer electrolytes and application in dye‐sensitized solar cell

Abstract: Poly(methyl acrylate) (PMA)-tetrapropylammonium iodide (TPAI) and poly(vinyl acetate) (PVAc)-TPAI solid polymer electrolytes were prepared by solution casting method. DSC, FTIR, and conductivity results are reported. TPAI interacts with PMA and PVAc to form PMA-TPAI and PVAc-TPAI complexes. Formation of PMA-TPAI and PVAc-TPAI complexes are supported by the DSC and FTIR studies. Linear relationship for the dependence of glass-transition temperature, T g , on salt concentration allows the estimation of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In another study it has been found that addition of a cross-linker in the polymer matrix can also reduce the polymer mobility or flexibility. 247 In general, the conductivity of the neat PMA membrane is approximately 0.9 × 10 −11 S cm −1 , which was augmented by the addition of a certain amount of TPAI to 2.6 × 10 −11 S cm −1 . 247 The improved ionic conductivity was due to the dissociation of TPAI, leading to the generation of more carrier ions, and the possibility of ionic mobility also increased meaningfully.…”
Section: 235mentioning
confidence: 98%
See 1 more Smart Citation
“…In another study it has been found that addition of a cross-linker in the polymer matrix can also reduce the polymer mobility or flexibility. 247 In general, the conductivity of the neat PMA membrane is approximately 0.9 × 10 −11 S cm −1 , which was augmented by the addition of a certain amount of TPAI to 2.6 × 10 −11 S cm −1 . 247 The improved ionic conductivity was due to the dissociation of TPAI, leading to the generation of more carrier ions, and the possibility of ionic mobility also increased meaningfully.…”
Section: 235mentioning
confidence: 98%
“…247 In general, the conductivity of the neat PMA membrane is approximately 0.9 × 10 −11 S cm −1 , which was augmented by the addition of a certain amount of TPAI to 2.6 × 10 −11 S cm −1 . 247 The improved ionic conductivity was due to the dissociation of TPAI, leading to the generation of more carrier ions, and the possibility of ionic mobility also increased meaningfully. However, after a certain limit of TPAI concentration in electrolyte solution results a significant reduction of ionic conductivity which is due to the ionic reassociation (due to the reduction of ionic distance) which also reduce the photovoltaic performance of the cell, a similar trend has also been found by Xie in his study.…”
Section: 235mentioning
confidence: 98%
“…Azmar et al also have incorporated tetrapropylammonium iodide (Prop 4 I) salt into PMA/PVAc-based GPE as the doping salt . It has reported the maximum efficiency to reach 9.67% with J SC of 22.91 mA cm –2 , V OC of 0.73 V, and FF of 58%.…”
Section: Available Alternatives: Polymer Electrolytesmentioning
confidence: 99%
“…The interaction between those atoms leads to a negative shifting of the conduction band edge of TiO 2 photoanode. N -Alkylbenzimidazole (NMBI) is another category of organic compounds (i.e., N -alkylbenzimidazole derivatives) that behave similarly to 4-TBP, where it also leads to an enhancement of the V OC value. , In contrast, the shifting of the conduction band of the TiO 2 photoanode reduces the energy difference between the exciting dye to the TiO 2 conduction band. This phenomenon can result in a less efficient electron injection, and thus, a smaller short-circuit current is produced. , Bandara et al .…”
Section: Available Alternatives: Polymer Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation